Electromagnetic Properties of Polypyrrole Metallic Magnetic Nanocomposites: First‐Principles Study. Issue 5 (3rd February 2022) - Wang, Yesong; Huang, Xinshu; Lu, Liying; Shi, Jing; Liu, Jiang
Abstract: Conductive polypyrrole (PPy) is an excellent polymer material for microwave absorption, which is vital for reducing electromagnetic interference (EMI) for electronic devices. To improve the microwave absorption capability and enhance the thermal stability and mechanical ductility of conductive PPy, metallic magnetic nanoparticles can be added to form PPy nanocomposites. In this paper, we present the first study to compute the electromagnetic properties of PPy nanocomposites based on the first principles method. It is discovered that (1) while doping can improve the microwave absorbing properties of PPy material, the absorption performance does not necessarily increase with the number of doping position; (2) conductivity and absorption coefficient increase significantly for the PPy nanocomposite compared with PPy. The dielectric loss is more than 2 at about 2 eV; (3) reflectivity and absorption coefficient decrease with the increase of PPy content in PPy/Co nanocomposite; (4) the average magnetic moment of the PPy nanocomposite is the same as that of pure nanoparticles, and this indicates that only nanoparticles generate magnetic loss for the nanocomposite. Abstract : To improve the microwave absorption capability and enhance the thermal stability and mechanical ductility of conductive polypyrrole (PPy), metallic magnetic nanoparticles can be added to form PPy nanocomposites. Herein, we present the first study to compute the electromagnetic properties of PPy nanocomposites based on the first principles method.